Menguji Kestabilan dan Kekonsistenan Metode Heun Pada Model Epidemi Susceptible, Exposed, Infected and Recovered Untuk Penyakit Demam Berdarah Dengue - Novalia, Essa; Nasution, Hamidah (Jurnal Sains Indonesia, 2018)
The Heun method is an improvement from the Euler method so that it has better accuracy, because in the Heun method, the solution of the Euler method is used as a predictor solution and then the initial estimation solution is corrected by the Heun method (corrector). In this study the method of Heun was used to complete the epidemic model of Susceptible, Exposed, Infected and Recovered (SEIR) of dengue fever while at the same time observing the stability and consistency of the Heun method. The observations of the Heun method are seen geometrically. From the results of the study it was found that the heun method was a stable and consistent method for finding solutions for almost the SEIR epidemic model. While from the data and completion of the approach obtained, the area of Medan Helvetia Subdistrict and Medan Sunggal District is an area that is endemic to dengue hemorrhagic fever. [TESTING THE STABILITY AND CONSISTENCY OF THE HEUN METHOD IN THE SUSCEPTIBLE, EXPOSED, INFECTED AND RECOVERED EPIDEMIC MODEL FOR DENGUE FEVER](J. Sains Indon., 42(1): 52-58, 2018)Keywords:Heun Method, Epidemic Model, Dengue Fever